Ferula Tadshikorum Pimenov Growth And Development In Different Soils - Halkuzieva Mokhira Asatullaevna (Genius Publishing Group, 2022)
This article reveals about medicinal and endemic plant Ferula tadshikorum M. Pimen which produces the valuable resin. As a result of non-compliance of resin producers with the rules of obtaining resin from plants, the natural reserves of resin-bearing ferules are declining sharply every year. In this regard, several decisions have been signed in the Republic to ensure the rational use and reproduction of these plants. In implementing these decisions, several experiments were carried out on the establishment of plantations of resin-bearing ferula species in arable lands. In order to determine the fertility of the F.tadshikorum in soils of different composition, in conditions of natural and moisture retention, we used seeds collected in August 2019 from the Dehkanabad forestry area of Kashkadarya region
Keywords: Plantation; plant; Ferula foetida; F. tadshikorum